Alloy composition for laser cladding remanufacturing and method for producing alloy coatings - Patents.com
Patent Information
- Application Number
- JP2024090917
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-12-27
- Filing Date
- 2024-06-04
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-06-04
AI Technical Summary
【0023】 有益な効果は、次のとおりである。本発明は、従来技術と比べて以下の利点を有する。
Smart Images

Figure 0007638569000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention belongs to the field of laser cladding remanufacturing and relates to a technique for producing alloy coatings, and more particularly to an alloy composition for laser cladding remanufacturing and a method for producing alloy coatings. [Background technology]
[0002] Diesel engines are one of the three main components that provide propulsion for ships and play a crucial role in the normal operation and continuous navigation of ships. Camshafts, as the core components of diesel engines, are prone to abnormal wear and corrosion during navigation, which poses a serious safety hazard to the normal navigation of ships and also causes huge economic losses due to the suspension of ship operations. In addition, old parts that are discarded when replaced with new parts cause a lot of resource waste and environmental pollution problems. Therefore, repair and remanufacturing of broken cam parts has become one of the core issues that we are focusing on.
[0003] Laser remanufacturing technology is one of the mainstream green remanufacturing processes that are being vigorously developed in China, and has the advantages of high manufacturing efficiency, less post-processing, excellent mechanical properties, small heat-affected area, etc. Laser cladding technology is a technology that uses a high-energy laser beam to rapidly melt and solidify alloy powder, which is a non-equilibrium solidification process in which complex physical and chemical reactions occur in the molten pool. Due to the rapid cooling and rapid heating forming characteristics of laser cladding, traditional alloy compositions are prone to defects such as pores and slag inclusions after being formed by laser cladding, which affects the use performance such as wear resistance and corrosion resistance of laser cladding remanufactured parts. High speed steel has the advantages of high hardness and high wear resistance, but due to the high carbon content and other alloy element content of high speed steel, serious cracks and segregation problems occur in the process of making alloy coating by laser cladding, which affects the use performance of laser cladding remanufactured parts. Therefore, according to the wear and corrosion failure mechanisms of diesel engine camshafts, the remanufacturing performance requirements, and the non-equilibrium solidification forming characteristics of laser cladding, designing a dedicated alloy composition for remanufacturing camshafts failed by wear and corrosion by laser cladding is the key to remanufacturing camshafts. Summary of the Invention
[0004] The object of the present invention is to overcome the shortcomings of the prior art by providing an alloy coating with excellent wear resistance and corrosion resistance due to the solid solution strengthening effect of various alloy elements, the fine grain strengthening effect due to grain size reduction, and the interaction between microstructures, thereby providing a new alloy composition and manufacturing process for repairing and remanufacturing components broken by wear or corrosion, and providing an alloy composition and a method for manufacturing an alloy coating for laser cladding remanufacturing, which has important practical significance in promoting the application of laser cladding technology in the field of remanufacturing.
[0005] As a technical solution, to achieve the above object, the present invention provides an alloy composition for laser cladding remanufacturing, the alloy composition comprising, in mass percentage, 0.8%-1.2% C, 5.0%-7.0% Cr, 9.0%-10.0% W, 4%-5% V, 4.0%-5.0% Co, 1.0%-2.0% Si, 3.0%-4.0% B, and the balance Fe.
[0006] Additionally, the alloy compositions are used in laser cladding repair and remanufacturing of components that have failed due to wear or corrosion.
[0007] The present invention further provides a method for preparing an alloy coating for laser cladding remanufacturing, said method comprising the steps of:
[0008] S1. Prepare and obtain an alloy powder for laser cladding according to the alloy composition and mass percentage.
[0009] S2, the alloy powder is placed on a pretreated 45# steel substrate.
[0010] S3, the alloy powder on 45# steel substrate is laser clad to form the alloy coating.
[0011] Furthermore, the alloy composition in step S1 contains, in mass percentages, C: 0.8% to 1.2%, Cr: 5.0% to 7.0%, W: 9.0% to 10.0%, V: 4% to 5%, Co: 4.0% to 5.0%, Si: 1.0% to 2.0%, B: 3.0% to 4.0%, and the balance Fe.
[0012] Furthermore, the method for preparing the alloy powder for laser cladding in step S1 is to weigh different alloy element powders by mass percentage, and use a ball mill to uniformly mix the mixed alloy element powders to obtain the alloy powder for laser cladding.
[0013] Furthermore, the grain size of the alloy element powder in step S1 is 30 to 70 μm.
[0014] Furthermore, the pretreatment method of the 45# steel substrate in step S2 is to use an angle grinder to remove impurities such as oxide scale on the surface of the 45# steel substrate to expose the metallic luster, use sandpaper to further polish the surface of the 45# steel substrate to a smooth and shiny state, and then use acetone and anhydrous ethanol in sequence to scrub the surface of the substrate to remove oil stains on the surface.
[0015] Furthermore, the alloy powder in step S2 is dried before being placed on the 45# steel substrate. Specifically, the alloy powder is placed in an air drying box and dried at 80 to 100°C for 1 to 2 hours.
[0016] Furthermore, the process parameters of the laser cladding in step S3 are: laser power 2000-2500W, scanning speed 4-6mm / s, powder layer thickness 0.5mm / layer, overlap rate 50%, spot diameter 3mm, argon gas protective gas, gas flow rate 2-5L / min.
[0017] Furthermore, the thickness of the alloy coating in step S3 is 1 to 2 mm.
[0018] In the present invention, a pre-alloyed powder production method is used in which the alloy powder is melted and solidified using a high energy laser beam, so that the clad coating and the 45# steel substrate form a good metallurgical bond, and the alloy clad coating has good formability and excellent wear resistance and corrosion resistance.
[0019] The innovative aspects of the present invention include the following:
[0020] The alloy clad coating forms a high-hardness eutectic boron carbide compound at the grain boundary during the laser cladding forming process, and the formation principle is as follows: the alloy composition provided by the present invention has a high content of B and C due to the specific content of B and C, and the solid solubility of B in γ-Fe is only 0.02%, and during the solidification process in the laser molten pool, after reaching the eutectic transition temperature, B will first be concentrated at the austenite grain boundary and combine with C to form a high-hardness eutectic boron carbide compound, which is achieved by the specific content and matching relationship of B and C in this application.
[0021] There is a solid solution strengthening effect, the principle of which is as follows: the present invention has a certain content of elements such as C, Cr, etc., and the content of elements such as C, Cr, etc. is high. In addition to forming boron carbide compounds in the alloy, the excess elements will be solid-solubilized in the crystal lattice, causing distortion of the crystal lattice and bringing about a strengthening effect.
[0022] The alloy cladding coating has a small grain size and plays the role of fine grain reinforcement, and its principle is as follows: 1) Laser cladding is a non-equilibrium solidification molding method with rapid heating and rapid cooling, and the cooling speed is very fast, so the structure solidifies without having time to grow, thereby forming a fine structure. 2) The eutectic boron carbide compound precipitated at the grain boundary during the solidification process of laser cladding prevents the growth of crystal grains, thereby forming a fine grain size.
[0023] The beneficial effects are as follows: The present invention has the following advantages over the prior art:
[0024] 1. The alloy clad coating obtained by the present invention has high hardness and excellent wear resistance. The alloy clad coating obtained by the present invention forms a eutectic boron carbide compound with high hardness at the grain boundary during the laser cladding forming process, and the microstructure of the clad layer is mainly martensite with high hardness, with a small amount of residual austenite. The content of alloy elements such as solid solution C and Cr in the alloy structure is high, which achieves the effect of solid solution strengthening, and the grain size of the alloy clad coating is small, which achieves the effect of fine grain strengthening. Through the combined effects of microstructure strengthening, solid solution strengthening and fine grain strengthening, the alloy clad coating achieves the effects of high hardness and excellent wear resistance. The average microhardness of the alloy clad coating is 840HV 0.2 The hardness of the cladding layer is 1.72×10, which is five times that of the substrate. -8 mm 3 / N·mm, which is three times the abrasion resistance of the substrate.
[0025] 2. The alloy clad coating obtained by the process has excellent corrosion resistance. Analysis of the electrochemical curve of the clad layer shows that the corrosion potential of the clad layer is significantly higher than that of the 45# steel substrate, and after electrochemical corrosion, there are a few corrosion pits on the surface of the clad layer, which can greatly improve the corrosion resistance of the failed components. [Brief description of the drawings]
[0026] [Figure 1] FIG. 2 is a diagram showing the laser formability morphology of the cladding layer. [Diagram 2] FIG. 4 is a microhardness curve diagram of a clad layer. [Diagram 3] FIG. 2 is an electrochemical Tafel curve diagram of the cladding layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The present invention will be further described below in combination with drawings and specific examples. However, it should be understood that these examples are only for the purpose of illustrating the present invention and are not intended to limit the scope of the present invention. After reading the present invention, modifications to various equivalent forms of the present invention by those skilled in the art are all included in the scope limited by the appended claims of this application.
[0028] Example 1: This example provides an alloy composition for laser cladding remanufacturing, which contains, by mass percentage, C: 0.8%, Cr: 5.0%, W: 9.0%, V: 4%, Co: 4.0%, Si: 1.0%, B: 3.0%, and Fe: 73.2%.
[0029] In this embodiment, the alloy composition is used for laser cladding repair and remanufacturing of camshafts in diesel engines that have failed due to wear and corrosion, and a method for producing an alloy coating for laser cladding remanufacturing is provided, the method comprising the steps of:
[0030] 1) Weigh different alloying element powders by mass percentage, and the particle size of the alloying element powder is 30-70 μm. Use a ball mill to uniformly mix the mixed alloying element powder at a rotation speed of 300 r / min and a mixing time of 8 h to obtain the alloying powder for laser cladding.
[0031] 2) Use an angle grinder to remove impurities such as oxide scale on the surface of the 45# steel substrate to expose the metallic luster, and use sandpaper to further polish the surface of the 45# steel substrate to a smooth and shiny state. Then use acetone and absolute ethanol in sequence to scrub the surface of the substrate to remove any oil stains on the surface.
[0032] 3) Place the alloy powder in a ventilation drying box and dry it at 100℃ for 1 hour.
[0033] 4) Using a powder spreading tool, pre-spray the dried alloy powder onto the pre-treated 45# steel substrate.
[0034] 5) Laser clad the alloy powder on 45# steel substrate to form an alloy coating.
[0035] The process parameters of laser cladding were: laser power 2000W, scanning speed 4mm / s, overlap rate 50%, spot diameter 3mm, argon gas protective gas, gas flow rate 2L / min, and powder layer thickness 0.5mm / layer.
[0036] The final alloy coating thickness is 1 mm.
[0037] Example 2: This example provides an alloy composition for laser cladding remanufacturing, which contains, by mass percentage, C: 1.2%, Cr: 7.0%, W: 10.0%, V: 5.0%, Co: 5.0%, Si: 2.0%, B: 4.0%, and Fe: 65.8%.
[0038] In this embodiment, the alloy composition is used for laser cladding repair and remanufacturing of camshafts in diesel engines that have failed due to wear and corrosion, and a method for producing an alloy coating for laser cladding remanufacturing is provided, the method comprising the steps of:
[0039] 1) Weigh different alloying element powders by mass percentage, and the particle size of the alloying element powder is 30-70 μm. Use a ball mill to uniformly mix the mixed alloying element powder at a rotation speed of 300 r / min and a mixing time of 8 h to obtain the alloying powder for laser cladding.
[0040] 2) Use an angle grinder to remove impurities such as oxide scale on the surface of the 45# steel substrate to expose the metallic luster, and use sandpaper to further polish the surface of the 45# steel substrate to a smooth and shiny state. Then use acetone and absolute ethanol in sequence to scrub the surface of the substrate to remove any oil stains on the surface.
[0041] 3) Place the alloy powder in a ventilation drying box and dry it at 80℃ for 2 hours.
[0042] 4) Using a powder spreading tool, pre-spray the dried alloy powder onto the pre-treated 45# steel substrate.
[0043] 5) Laser clad the alloy powder on 45# steel substrate to form an alloy coating.
[0044] The process parameters of laser cladding were: laser power 2500W, scanning speed 6mm / s, overlap rate 50%, spot diameter 3mm, argon gas protective gas, gas flow rate 5L / min, and powder layer thickness 0.5mm / layer.
[0045] The final alloy coating thickness is 2 mm.
[0046] Example 3: This example provides an alloy composition for laser cladding remanufacturing, which contains, by mass percentage, C: 1.0%, Cr: 6.0%, W: 9.5%, V: 4.5%, Co: 4.5%, Si: 1.5%, B: 3.6%, and Fe: 69.4%.
[0047] In this embodiment, the alloy composition is used for laser cladding repair and remanufacturing of a camshaft of a diesel engine that has failed due to wear or corrosion, and a method for producing an alloy coating for laser cladding remanufacturing is provided, the method comprising the steps of:
[0048] 1) Weigh different alloying element powders by mass percentage, and the particle size of the alloying element powder is 30-70 μm. Use a ball mill to uniformly mix the mixed alloying element powder at a rotation speed of 300 r / min and a mixing time of 8 h to obtain the alloying powder for laser cladding.
[0049] 2) Use an angle grinder to remove impurities such as oxide scale on the surface of the 45# steel substrate to expose the metallic luster, and use sandpaper to further polish the surface of the 45# steel substrate to a smooth and shiny state. Then use acetone and absolute ethanol in sequence to scrub the surface of the substrate to remove any oil stains on the surface.
[0050] 3) Place the alloy powder in a ventilation drying box and dry it at 90℃ for 1.5 hours.
[0051] 4) Using a powder spreading tool, pre-spray the dried alloy powder onto the pre-treated 45# steel substrate.
[0052] 5) Laser clad the alloy powder on 45# steel substrate to form an alloy coating.
[0053] The process parameters of laser cladding were: laser power 2300W, scanning speed 5mm / s, overlap rate 50%, spot diameter 3mm, argon gas protective gas, gas flow rate 4L / min, and powder layer thickness 0.5mm / layer.
[0054] The final alloy coating thickness is 1.5 mm.
[0055] In order to verify the validity and actual effect of the solution of the present invention, in this embodiment, the hardness, wear rate and electrochemical corrosion performance of the alloy clad coatings prepared in Example 1, Example 2 and Example 3 are tested respectively, and the specific test results and analysis are as follows:
[0056] (1) Analysis of formability of alloy clad coating The alloy clad coatings of Examples 1 to 3 all exhibit good laser formability, and the alloy clad coatings have no obvious defects such as cracks, pores, and slag inclusions, and the macroscopic and cross-sectional morphologies of the clad layers are shown in FIG.
[0057] (2) Analysis of the microstructure of alloy clad coating The microstructure of the alloy clad coatings in Examples 1 to 3 is mainly martensite, grain boundary boron carbide compounds and a small amount of retained austenite. Due to the different cooling rates of the alloy clad coatings in different laser cladding processes, the content of the microstructure in the alloy clad coatings in different examples changes slightly.
[0058] (3) Microhardness analysis of alloy clad coating The microhardness curves of the alloy clad coatings of Examples 1 to 3 are shown in Figure 2. From Figure 2, it can be seen that the hardness curves are composed of the alloy clad coating, the heat-affected zone, and the substrate. The average hardness of the alloy clad coating of Example 1 is 840HV 0.2 The average hardness of the alloy clad coating of Example 2 is 880HV 0.2 The average hardness of the alloy clad coating of Example 3 is 830HV 0.2 This is about five times higher than the hardness of the substrate (173 HV).
[0059] (4) Analysis of wear resistance of alloy clad coating In the wear resistance test of the alloy clad coating of Examples 1 to 3, Al2O3 was used as the friction pair, the wear load was 10N, the friction method adopted was reciprocating friction and wear method, and the wear time length was 60min. A white light interferometer was used to measure the wear volume of the clad layer, and the calculated wear rates of Examples 1 to 3 were 1.72 × 10 -8 mm 3 / N mm, 2.38×10 -8 mm 3 / N·mm and 2.51×10 -8 mm 3 / N·mm, and the wear resistance ratio is 45# steel substrate (8.22×10 -8 mm 3 / N·mm), which is three times higher. Analysis of the wear morphology of the alloy clad coatings reveals that the wear mechanisms of the alloy clad coatings in Examples 1 to 3 are a mixed wear mechanism consisting of abrasive wear, adhesive wear, and oxidative wear.
[0060] (5) Analysis of the corrosion resistance of the clad layer The electrochemical Tafel curves of the alloy clad coatings of Examples 1 to 3 are shown in FIG. 3. The corrosion potential and corrosion current density of the alloy clad coatings of Examples 1 to 3 were analyzed using an epitaxial method. The corrosion potentials of the alloy clad coatings of Examples 1 to 3 were −520 mV, −506 mV, and −560 mV, respectively, and the corrosion current densities were 2.58E-5 A / cm. 2 , 2.98E-5A / cm 2 and 2.67E-5A / cm 2 The alloy clad coatings all exhibit good corrosion resistance, and the analysis of the corrosion morphology of the samples after electrochemical testing shows that there are a few corrosion pits on the surface of the alloy clad coatings, and the corrosion mechanism is pitting corrosion.
Claims
1. 1. An alloy composition for use in laser cladding, comprising: An alloy composition comprising, by mass percentage, 0.8% to 1.2% C, 5.0% to 7.0% Cr, 9.0% to 10.0% W, 4% to 5% V, 4.0% to 5.0% Co, 1.0% to 2.0% Si, 3.0% to 4.0% B, and the balance being a mixed powder of Fe.
2. 10. The alloy composition of claim 1, wherein the alloy composition is used for repairing components that have failed due to wear or corrosion by laser cladding.
3. 1. A method for preparing an alloy coating for repair by laser cladding, comprising: Step S1: preparing an alloy powder for laser cladding according to a mass percentage as an alloy composition; Step S2: placing the alloy powder on a pretreated S45C (45# steel) substrate; Step S3 of laser cladding the alloy powder on a S45C (45# steel) substrate to form an alloy coating; The alloy composition in step S1 includes, by mass percentage, C: 0.8% to 1.2%, Cr: 5.0% to 7.0%, W: 9.0% to 10.0%, V: 4% to 5%, Co: 4.0% to 5.0%, Si: 1.0% to 2.0%, B: 3.0% to 4.0%, and the balance is Fe; The method for preparing alloy coating for repair by laser cladding, wherein the process parameters of laser cladding in step S3 are: laser power 2000-2500W, scanning speed 4-6mm / s, overlap rate 50%, spot diameter 3mm, argon gas protective gas, gas flow rate 2-5L / min, powder layer thickness 0.5mm / layer.
4. The method for preparing alloy coating for repair by laser cladding as described in claim 3, characterized in that in step S1, the method for preparing alloy powder for laser cladding is to weigh different alloy element powders by mass percentage, and use a ball mill to uniformly mix the alloy element powders to obtain alloy powder for laser cladding.
5. The method for preparing an alloy coating for repair by laser cladding according to claim 4, characterized in that the grain size of each powder as the alloy composition in step S1 is 30-70 μm.
6. The method for preparing an alloy coating for repair by laser cladding according to claim 3, characterized in that the pretreatment method of the S45C (45# steel) substrate in step S2 is to use an angle grinder to remove impurities on the surface of the S45C (45# steel) substrate to bring out metallic luster, to further polish the surface of the S45C (45# steel) substrate to a smooth and shiny state using sandpaper, and to sequentially rub the surface of the substrate using acetone and absolute ethanol to remove oil stains on the surface.
7. The method for preparing an alloy coating for repair by laser cladding as described in claim 3, characterized in that the alloy powder in step S2 is dried before being placed on the S45C (45# steel) substrate, specifically, the alloy powder is placed in an air drying box to dry.
8. The method for preparing an alloy coating for repair by laser cladding according to claim 3, characterized in that the thickness of the alloy coating in step S3 is 1-2 mm.
Citation Information
Patent Citations
Method for manufacturing metallic component by additive laser manufacturing method
JP2015066599A
Powder for metal mold
JP2019173049A
Abrasion-resistant and corrosion-resistant iron based alloy powder for laser cladding, and laser cladding layer therefrom
JP2021110037A
Metal alloy compositions and applications thereof
US20130266798A1
Iron-based metal powder for ultra-high-speed laser cladding, its preparation method and its application
US20210207251A1